On the Quest for Oxygen Evolution Reaction Catalysts Based on Layered Double Hydroxides: An Electrochemical and Chemometric Combined Approach - Isacco Gualandi; Elisa Musella; Giulia Costa; Massimo Gazzano; Erika Scavetta; Sergio Zappoli; Domenica Tonelli (Advanced Energy & Sustainability Research)
The oxygen evolution reaction (OER) is a crucial process in various energy conversion and storage technologies, such as water electrolysis. Developing efficient and cost‐effective electrocatalysts is essential to achieve the commercialization of devices for the transition toward sustainable energy solutions. Herein, ternary layer double hydroxides (LDHs) are synthesized and characterized as electrocatalysts for OER using a potentiodynamic electrochemical deposition method on Grafoil. A chemometric approach based on experimental design is employed to rationalize the effort in the investigation of the LDHs which are based on Ni, Co, and Fe. The deposited films are characterized using cyclic voltammetry and X‐ray diffraction to determine peak currents and potentials, and crystal size. Furthermore, the electrocatalyst performances are assessed by linear sweep voltammetry in 1M KOH from which the Tafel slope and onset potential are calculated. The obtained data are used to derive models describing the material properties and electrocatalyst performance as a function of the electrolyte composition used during the LDHs electrodeposition. This study provides valuable insights into the relationship between the electrocatalyst composition and its OER activity, enabling the design of more efficient and sustainable electrochemical systems for energy applications.